Evaluasi Penggunaan Fingerprint pada Karyawan Back Office Hotel - Luh Hari Susanti; Poppy Indriani; Margriet Puspa Dewi (TIN: Terapan Informatika Nusantara, 2026)
This study aims to assess the implementation of a fingerprint attendance system among back-office employees at Wyndham Opi Hotel Palembang and to examine its influence on work discipline. The findings indicate that the fingerprint-based system has been implemented effectively and is considered more efficient than the previous manual attendance method. The system records employee attendance automatically and objectively, ensuring greater orderliness while reducing recording errors and minimizing the risk of data manipulation. The adoption of fingerprint technology has contributed positively to employee discipline, particularly in fostering greater awareness of working hours and punctuality. Nevertheless, the improvement in discipline has not yet reached its full potential. This limitation is associated with employees’ adaptation to the new system, certain technical constraints under specific conditions, and the absence of integration between attendance data and performance appraisal mechanisms, including the rewards and sanctions applied within the organization. From the perspective of Expectancy Theory, the effectiveness of a fingerprint attendance system will be enhanced when employees clearly understand that punctual attendance is directly linked to performance evaluation, incentives, and disciplinary consequences. Therefore, the fingerprint system should not be viewed merely as an administrative instrument, but also as a strategic mechanism that supports the development of disciplined work behavior among employees.